ANTI-JESUITISM AT THE SOUTH OF THE WORLD. RELIGIOUS POLEMICS ABOUT THE COMPANY OF JESUS IN PUERTO MONTT, CHILE (1859-1919) - Hernández Paredes, Ricardo (Revista de Historia Social y de las Mentalidades, 2017)
The activities of the Jesuits, their social influence and the adverse reactions that provoke are frequently of interest for historians. Thus many investigations take their actions in the capital city, Santiago de Chile, as their matter. Nonetheless, other Jesuit community existed in Puerto Montt city during XIX Century, and is less known. This investigation tries to describe their characteristics, similarities and differences with its pair of Santiago, pointing to expose and interpret rejecting expressions (anti-Jesuitism) that appear by their presence there in the south, seen through press, the principal source preserved. Puerto Montt city, founded in 1853, thousand km southward from the capital, received a community of jesuits in 1859 who came from Germany, with a last rector finish-ing in 1919. Since their beginnings they starred important missionary and educational ac-tivities, with acknowledged esteem among their loyal supporters. However, ideological rejection joined them always from the hostile press. The discoveries were abundant, intense, revealing old dated European ideological influence. They mark a special section in the global phenomenon of Anti-Jesuitism.